Formation of Students' Morals Through Clanting Values of Tasawuf in Islamic Boarding Schools - Deden Syarif Hidayatulloh; Fuad Hilmi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Morals are not only important for individual development, but also for the welfare and progress of society as a whole. Instilling Sufi values in everyday life, especially in the Shahida Islamic boarding school environment, can help students develop strong moral values in accordance with the provisions of the Shari'a and Islamic teachings. Islamic boarding schools are also known as workshops for becoming fully human. So that students at the Shahida Islamic boarding school learn Sufism. The method used in this research is a qualitative case study approach. Two methods were used to collect research data, namely interviews and observation. The result of this research is that, through the example of all parties, studying the book of Sufism, and implementing and practicing the sunnah, can foster noble morals in students. The research concludes that instilling moral values through Sufi values has a positive impact on students' spiritual development, both individually and in society.